2009
DOI: 10.1080/09638230701879102
|View full text |Cite
|
Sign up to set email alerts
|

Working with interpreters across language and culture in mental health

Abstract: Background: Mental health professionals need to be able to work effectively with interpreters to promote good clinical practice and ensure equality of access and service delivery as well as meet the requirements of European law. The process offers practitioners an opportunity to enrich their understanding of the diverse idioms of distress, cultural constructions and explanatory health beliefs. Aims: This paper draws upon the literature and clinical accounts to provide a set of positive practice guidelines on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 27 publications
6
62
0
8
Order By: Relevance
“…3. Suggestions about the specific dilemmas of working with an interpreter in the context of relationship and sexual problems are discussed here, the interested reader is referred for detailed good practice guidelines on working with interpreters in a ''mental health'' or therapeutic context to Tribe and Lane (2008) or to the Good Practice Guidelines written for psychologists working in health settings to be found from Autumn (2008) on the British Psychological Society website: www.bps.org.uk 4. The two case studies presented here are based on real cases but in order to ensure clients' anonymity all personal details have been removed and particularities such as gender, presenting problems, place of origin have been changed.…”
Section: Resultsmentioning
confidence: 99%
“…3. Suggestions about the specific dilemmas of working with an interpreter in the context of relationship and sexual problems are discussed here, the interested reader is referred for detailed good practice guidelines on working with interpreters in a ''mental health'' or therapeutic context to Tribe and Lane (2008) or to the Good Practice Guidelines written for psychologists working in health settings to be found from Autumn (2008) on the British Psychological Society website: www.bps.org.uk 4. The two case studies presented here are based on real cases but in order to ensure clients' anonymity all personal details have been removed and particularities such as gender, presenting problems, place of origin have been changed.…”
Section: Resultsmentioning
confidence: 99%
“…Culturally and linguistically diverse (CALD) individuals (who identify as having certain cultural or linguistic affiliations by virtue of their place of birth, ancestry or ethnic origin, religion, or preferred or spoken language) are generally underserved by health services, experience an unequal burden of disease, confront cultural and communication barriers to accessing appropriate services and receive a lesser quality of care than the remainder of the population [2][3][4][5][6][7][8]. Cultural competency is a common approach to promoting better health for service users from CALD and other minority groups [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The interpreter functions as the mouth piece for the therapist and client and offers no cultural interpretations of the content of the conversation (Dysart-Gayle, 2005). However, studies have found that most medical and Downloaded by [Umeå University Library] at 15:22 03 April 2015 WRIGHT mental health professionals reported the conduit role was too restrictive in their work with LEP clients (Hsieh & Hong, 2010;Tribe & Keefe, 2009;Tribe & Lane, 2009;Yakushko, 2010). They suggested that the conduit/transmission role was culturally insensitive, as many English idioms lost their meaning in translation (Dysart-Gale, 2005;NCIHC, 2004;Tribe & Keefe, 2009).…”
Section: Multiple Roles Utilized By Interpretersmentioning
confidence: 92%
“…The literature describes three different roles often held by spoken language interpreters: conduit/transmission, cultural broker, or advocate (Dysart-Gale, 2005NICHC, 2004;Tribe & Keefe, 2009;Tribe & Lane, 2009;Yakushko, 2010).…”
Section: Multiple Roles Utilized By Interpretersmentioning
confidence: 99%